Interactive and Immersive Advertising in the Metaverse: User Perceptions and Engagement Compared to Traditional Online Environments - Szeberényi, András; Akbar, Soltani; Araz, Najafloo; Balku, Róbert (Acta Carolus Robertus, 2025)
Despite the growing interest in the Metaverse as a marketing platform, significant gaps remain in understanding how users perceive and engage with advertising in immersive virtual environments. While prior research has explored theoretical frameworks and business strategies for Metaverse advertising, empirical evidence from the user perspective is limited, particularly regarding comparative effectiveness against traditional digital advertising. This study addresses this gap by examining how the immersive and interactive characteristics of the Metaverse influence user engagement and brand experience compared to traditional online marketing environments. An online questionnaire was distributed in Facebook Metaverse groups between November 2024 and January 2025, collecting 252 valid responses primarily from Generation Y and Generation Z users. The survey assessed familiarity with the Metaverse, exposure to advertisements, preferred advertising formats, attitudes toward Metaverse advertising, user engagement intentions, and comparative perceptions of immersion, interactivity, personalization, social influence, and novelty. Data analysis employed descriptive statistics and one-way ANOVA to identify significant differences across demographic groups. Results demonstrate that Metaverse advertising significantly outperforms traditional online advertising across key metrics. Interactive experiences emerged as the most preferred advertising format, with 76.2% of respondents having encountered Metaverse advertisements. Users perceived Metaverse ads as more engaging, more memorable, and less intrusive than traditional online ads. Statistical analysis revealed significant age-related differences: Millennials and Generation Z rated Metaverse advertising as significantly more engaging and memorable than older users. Personalization emerged as the strongest influence factor, followed by novelty and interactivity. These findings contribute empirical evidence to the emerging field of Metaverse marketing by demonstrating quantifiable advantages of immersive advertising. Businesses seeking to leverage Metaverse platforms should prioritize interactive and personalized experiences while targeting younger, digitally native audiences. Future research should examine long-term engagement patterns and cross-cultural differences in Metaverse advertising effectiveness.